Measuring performance towards sustainable consumption and production : types of indicators and indicator sets - Lutter, Stephan; Pirgmaier, Elke; Frühmann, Johannes; Burger, Eva; Mayr, Magdalena; Polzin, Christine; Pascoe, Claire (CSCP, 2009)
"Authors: Stephan Lutter, Elke Pirgmaier, Johannes Frühmann, Eva Burger, Magdalena Mayr, Christine Polzin (SERI) ; Editor: Claire Pascoe This report has been prepared ... as part of the Action Town - Research and Action for Sustainable Consumption and Production (officially called CSOContribution2SCP) project"